Effect of Temperature on Free Vibration of Functionally Graded Plate With Cutout - Badiganti, Chandra Mouli; Kumar, K Kishor; Leelapali, Shiva; Prasanth, I.S.N.V.R.; Krishna, Jogi (International Journal of Integrated Engineering, 2021)
Present article performs the parametric study on vibration characteristics of functionally graded (FG) plate with central hole in thermal environment. ANSYS Parametric Design language is used in developing Finite element model and discretization of the material is done using an eight-node serendipity shell element. Displacement field of the present model is developed using first-order shear deformation theory (FOSDT) with six degrees of freedom. Frequency responses are extracted using Block Lanczos eigenvalue extraction method. To show the accurateness of the model developed convergence study is done for various mesh sizes to obtain the suitable mesh density. Present results which are computed are compared and validated with the previously reported results. Finally, the effect of temperature on various parameters like cut-out size to thickness ratio, cut-out size to side ratio, power law index, side to thickness ratio, boundary conditions are shown through various numerical illustrations.